Development and validity of the Motivation Assessment Tool for Physical Education (MAT-PE) among young children. (May 2021) - Fitton Davies, K.; Watson, P.M.; Rudd, J.R.; Roberts, S.; Bardid, F.; Knowles, Z.; Foweather, L.
Abstract: Introduction: It is important to understand young children's motivation within Physical Education (PE) so that researchers and teachers can effectively support children's physical, affective, social and cognitive development as well as physical activity (PA) behaviors. However, there is a dearth of motivation research in PE with children under the age of seven due to a lack of developmentally appropriate assessment tools. Aims: This multi-study paper outlines the development, content and construct validity of a novel, mixed-method tool to assess young children's psychological needs and behavioral regulation within PE (Motivation Assessment Tool for Physical Education; MAT-PE). Methods: Study 1 consisted of the iterative development of the MAT-PE through working with 43 young children (ages 5–6) from three primary schools located within a large city in North West England. MAT-PE version 1 was subsequently examined for content validity in 85 children (ages 5–6) from 12 primary schools located within a large city in North West England and nine independent researchers with expertise in self-determination theory. Study 2 consisted of the development, content validation, acceptability and inter- and intra-rater reliability of the MAT-PE codebook. Study 3 explored construct validity through hypothesis-testing via correlational data. Descriptive data captured through the MAT-PE and codebook with 78 children (ages 5–6) from 12 primary schools located within a large city in North West England is also presented. Findings: The MAT-PE and its codebook were judged to have promising content validity, the codebook was deemed acceptable, as well as demonstrating excellent inter- and intra-rater reliability (ICC = 0.90). Regarding construct validity, as hypothesised, all psychological needs were positively correlated and autonomous regulations were negatively associated with amotivation. There were also unexpected correlations such as the negative correlation between intrinsic and identified regulation. Conclusion: Further development of the MAT-PE is required; nevertheless, this study has taken a promising first step in developing a tool to comprehensively measure five-to six-year-old children's motivational perceptions in PE. Highlights: Developed the Motivation Assessment Tool for Physical Education (MAT-PE). Assesses basic psychological need satisfaction and behavioral regulation in PE. Mixed method assessment suitable for use with young children (5-6 years old). Initial findings demonstrate that the MAT-PE has promising validity. More research is required to further develop and improve the MAT-PE.